Urgensi Digital Marketing terhadap Strategi Pemasaran Bagi UMKM Pasca Pandemi Covid-19 - Nor Maysari; Adullah Zawawi; Hadi Ismanto (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2020)
The Covid-19 pandemic that emerged at the end of 2018 from the outbreak had a significant impact on Indonesia. Work from home or working from home by utilizing the internet has succeeded in becoming the choice of many sectors in carrying out activities, especially in the economic sector. From this problem, MSMEs as the driving force of the Indonesian economy that cannot compete are threatened with a massive deficit to close their businesses. This study uses library search, with data sourced from books, results of previous studies, government databases, and internet pages and uses qualitative research by presenting accurate sources to describe problems based on data. The result of this research is the recovery of MSME-level business by utilizing technology for a marketing strategy entitled a comfortable digital marketing system. This innovation relies on creativity and quality based on tangible evidence. The contribution of MSMEs with digital-based mediators in marketing is believed to be able to restore the movement of the Indonesian economy after the Covid-19 pandemic and become a solution that can restore the economy in Indonesia.